A modified mix design method for pervious concrete based on Mohr-Coulomb failure criterion. (1st February 2021) - Yu, Fan; Sun, Daquan; Sun, Guoqiang; Ling, Senlin; Hu, Mingjun; Ma, Jianmin
Highlights: Mohr-Coulomb failure criterion can be used to describe the behavior of pervious concrete. With the decrease of the thickness of cement paste, the cohesion first increase, and then decrease slightly. A modified mix design method based on Mohr-Coulomb failure criterion was proposed by introducing the aggregate content coefficient (ACC). Abstract: Large porosity and connected porous structure enables pervious concrete to obtain water permeability, but significantly decreases its strength. It is still a critical challenge for the mix design of pervious concrete to well balance its permeability and strength. The purpose of this paper is to study the strength mechanism of pervious concrete and propose a modified mix design method based on Mohr-Coulomb failure criterion. Five groups of samples with different aggregate-cement ratio varied from 5:1 to 4:1 were prepared (target porosity was 20%). The triaxial tests were applied to investigate the axial compression of these pervious concrete samples at different confining pressure. The results show that Mohr-Coulomb failure criterion can be used to describe the behavior of pervious concrete with compression. With the decrease of the thickness of cement paste, the cohesion first increase, and then decrease slightly. At the same porosity, the cementitious paste thickness was largely determined by aggregate content coefficient ( ACC ). A modified mix design method based on Mohr-Coulomb failure criterion was put forward by introducing the aggregate content coefficient ( ACC ). It was observed that ACC had little influence on porosity, pore area and fractal dimension of pervious concrete, and pervious concrete with different ACC had similar permeability. The strength increased with the decrease of ACC, but the growth rate was gradually decreasing. For the case in this paper, 0.94 was found to be the optimal value for ACC. By the modified mix design method, pervious concrete gained a similar permeability but obviously improved strength compared to the pervious concrete designed by conventional method.